Revisiting the Pedagogy of Teaching - Learning: Students’ Perspective - Devi, C. Renuga (Indian Journal of Educational Technology, 2021)
Pedagogy of teaching refers to the way teachers deliver the content of the curriculum to a class. Designing pedagogies that produce meaningful learning through educational concepts, competencies, content, evaluation, learning and teaching practices is paramount. Learning is dependent on the pedagogical approaches that teachers use in the classroom. Online Learning during this pandemic has changed much more than the content and approaches. The digital generation and the changes taking place in the present scenario like COVID 19 lockdown, technological advancements in teaching learning and flexibility in learning demands for innovation in teaching. This article brings out the need for revisiting the pedagogy of teaching - learning process on par with the changing educational scenario from the perspective of students. A sample of 97 students undergoing B.Ed and M.Ed Special Education courses in various specializations from the state of Tamil Nadu recorded their views upon the unanticipated transformation in the teaching learning process and its outcome in developing their knowledge and accessibility of resources. Findings of the study suggest that teachers have to augment their skills according to the emerging trends and untangle their conventional pedagogical approach in teaching by adapting to the technological changes.